Natural chemotherapeutic alternatives for controlling of haemonchosis in sheep - Mravčáková, Dominika; Váradyová, Zora; Kopčáková, Anna; Čobanová, Klaudia; Grešáková, Ľubomíra; Kišidayová, Svetlana; Babják, Michal; Dolinská, Michaela Urda; Dvorožňáková, Emília; Königová, Alžbeta; Vadlejch, Jaroslav; Cieslak, Adam; et al. (BMC veterinary research, 2019)
BACKGROUND: Parallel in vitro and in vivo experiments were designed to evaluate promising chemotherapeutic alternatives for controlling haemonchosis in ruminants. In vitro anthelmintic activities (egg hatch test - EHT; larval development test - LDT) of aqueous and methanolic herbal extracts Mix1 and Mix2 were investigated. The in vivo effects of dietary supplementation with Mix1 and Mix2 on the parasitological status, inflammatory response, antioxidant parameters and microbial community of the lambs infected experimentally with Haemonchus contortus were investigated. Lambs were divided into four groups for the in vivo study: uninfected control lambs (C), infected lambs (I), infected lambs supplemented with Mix1 (I + Mix1) and infected lambs supplemented with Mix2 (I + Mix2). The experimental period was 70 days. RESULTS: The number of eggs per gram (EPG) of feces was quantified 22, 30, 37, 44, 51, 58, 65 and 70 days post-infection, and mean abomasal worm counts were assessed 70 days post-infection. Quantitative analyses identified 57.3 and 22.2 mg/g phenolic acids, 41.5 and 29.5 mg/g flavonoids and 1.4 and 1.33 mg/g protoberberine-type alkaloids in Mix1 and Mix2, respectively. The methanolic extracts of the herbal mixtures in both in vitro tests had higher anthelmintic effects (P < 0.01) than the aqueous extracts, but the effects did not differ significantly between Mix1 and Mix2 (P > 0.05). I + Mix1 and I + Mix2 lowered mean EPGs between 44 and 70 d by 58.1 and 51.6%, respectively. The level of IgG antibodies against H. contortus increased significantly after infection in each infected group. CONCLUSION: These results represent the first monitoring of the in vitro anthelmintic effects of herbal mixtures on H. contortus. The in vivo experiment indicated that the anthelmintic effect was not sufficient for the elimination of parasites, but this herbal treatment may affect the host over a longer term, reducing the parasitic infection in the host.
Keywords: 16S rRNA gene; hemonchóza; Sheep; Plants, Medicinal; Female; Parasite Egg Count; zvířata; Haemonchus; Haemonchiasis; počet parazitárních vajíček; Total antioxidant capacity; Sheep Diseases; ženské pohlaví; Phytochemicals; UHRMS; biologické přípravky; Animals; léčivé rostliny; Haemonchus contortus antigen; nemoci ovcí; Biological Products; ovce